An assessment of China's approach to Freedom of Association and the Right to Collective Bargaining against international labour standards: should African countries be concerned? - Newby, Christopher (Department of Public Law, 2022)
In recent years, the People's Republic of China has been expanding its presence in Africa and developing enterprises across the African continent. China is now one of the largest investors and trading partner in Africa. The impact of this investment on labour standards, and the expectation of Chinese investors in this regard, is likely to be a concern for host countries. The purpose of this study is to consider whether China's approach to freedom of association and the right to collective bargaining is compatible with international labour standards, which have been ratified by most African countries. This is achieved by comparing the relevant laws in China, that regulate freedom of association and collective bargaining, against the international standards set by the International Labour Organisation's (ILO) Conventions and Recommendations. In particular, the provisions of the Freedom of Association Convention (No. 87) and the Collective Bargaining Convention (No .98), among others, together with the findings of the ILO Committee on Freedom of Association, are used to determine an international standards ‘comparator'. The Chinese Labour Law, Trade Union Law and Labour Contract Law are subsequently evaluated against this comparator in order to determine the extent of compliance of the Chinese labour system with international labour standards. The outcome of the comparison shows a broad degree of compliance with international standards relating to the formal recognition in law of the rights to freedom of association and collective bargaining as well as the identification of vulnerable classes of workers such as women, migrant workers and rural workers. However, two major discrepancies in the Chinese legal system were found: first, in relation to trade unions - the existence of one centralised representative organisation known as the All-China Federation of Trade Unions (ACFTU), with overarching authority, infringes the establishment, autonomy, independence and functioning of smaller grass-roots trade unions. Second, the right to strike was found to be suppressed in China. Ultimately, the Chinese formulation of the right to freedom of association and the exercise thereof is inherently different to the international standards. The right is conceptualised and practiced within the Chinese socialist market economy under the guidance of the Communist Party which is the supreme power in the democratic dictatorship. Therefore, the Chinese experience and understanding of the right to freedom of association and the right to strike may be fundamentally different to African states in terms of its content, ideological underpinning, exercise and enforcement. These findings demonstrate a need for African countries that host Chinese investment to proactively guard against the labour rights violations that may occur due to the differing domestic legal frameworks.